OC-009 Spyglass DS™ Cholangioscopy for Difficult Stones: Early Experience of Two UK Centres. (17th August 2016) - Bekkali, NL; Sturgess, R; Dwyer, L; Direkze, S; Webster, GJ
Abstract : Introduction: Endoscopic clearance of bile duct stones is achievable in >90% with conventional ERCP (ASGE 2015). Additional techniques may be necessary for those patients with difficult stones, which may be due to stone location, size, or number. Cholangioscopy and intraductal lithotripsy may have a specific role in treating difficult stones. The Spyglass DS™ peroral cholangioscopy system was introduced in mid-2015, and here we report our early experience with this technique. Methods: Spyglass DS cholangioscopy was available in the UK from May 2015. Cases referred to our 2 centres were assessed within a specialist HPB multidisciplinary meeting, and all cases deemed appropriate for Spyglass DS were prospectively followed. Patient demographics, indication for cholangioscopy, technical outcome and complications were recorded. Results: Eight-four patients (54% female, median age 61 years (range 25–90)) underwent ERCP with plan for cholangioscopy. Indications were stones (83%), strictures (14%) and other (3%). The stones were extrahepatic (62%), intrahepatic (15%), cystic duct (15%), and intra + extrahepatic (8%). The total number of stones was <5 in 58%, 5–10 in 18%, 11–15 in 9%, 16–20 in 9% and >20 stones in 6%. The 70 patients with stones had undergone a median 2 ERCPs (range 1–7) prior to referral. At our centres duct clearance was achieved in 30% (n = 21/70) without need for cholangioscopy, using combinations of extraction balloon (100%), sphincteroplasty (69%) and mechanical lithotripsy (ML) (54%). Cholangioscopy was needed for 49 cases, in 46 patients. Cholangioscopy with electrohydraulic lithotripsy (EHL) led to complete stone clearance in 72% of patients (33/46), of whom 3 on second EHL. The remaining patients await a second EHL procedure. In the 18 patients with unsuccessful stone clearance to date, reasons included: stone size + density (n = 8 with stones >15 mm); intrahepatic stones (n = 9); inability to apply EHL (n = 1). Overall, stone clearance was achieved in 54/67 (81%) of patients undergoing ERCP +/- cholangioscopy with EHL. The mean (SD) duration of ERCP + cholangioscopy + EHL was 93 (±28) minutes; 90% had propofol sedation, and 10% conscious sedation. No complications were observed. Conclusion: In patients who have failed multiple attempts at endoscopic stone clearance, referral to a centre with availability of Spyglass DS cholangioscopy and EHL results in definitive stone clearance in 81% of patients. This success includes further conventional ERCP. Stone clearance with cholangioscopy may be achieved irrespective of site or size of stones, but failure of complete fragmentation with EHL may contribute to need for repeat procedures, and occasional failure. Disclosure of Interest: None Declared